A capelania hospitalar: uma contribuição na recuperação do enfermo oncológico - Silva, Alexsandro Coutinho da (2010)
This research aims to investigate the contribution that the service can provide pastoral care to the sick cancer and their families in the hospital. In this paper, we seek to recover the human dimension by means of spirituality, be a reference to aid in the face of pain and suffering to convey the love and consolation and hope in God exists, to offer health professionals a better understanding of the importance of hospital chaplaincy service to aid in the recovery of the patient. Thus, in the first chapter it s indicated an objective way to its origin, history and development of pastoral care to the current context. Addresses the question of evangelical statement of pastoral care, as well as the profile of the hospital chaplain. The second part discusses a priori on the issue of dialogue between theology and science. And the philosophy part of this dialogue as a mediator between these knowledge. In a second step the author addresses the concepts integral health and salvation, and finally presents several studies showing the benefits of faith to health. In the third chapter, in turn provides a reflection on the question of the drama experienced by cancer patients. Addresses concisely spirituality of cancer patients in the hospital.